The Ethical Evaluation of Corporate Moral Intelligence in Promoting Strategic Human Resource Development and Organizational Agility in Thailand - Boonyakiate, Kemisa (Digital Repository of Theses, 2024)
This dissertation presents an in-depth exploration of Corporate Moral Intelligence (CMI) and its profound influence on Strategic Human Resource Development (SHRD) and Organizational Agility (OA) within the context of Thai Small and Medium-sized Enterprises (SMEs). This study fills a crucial gap in the existing literature by adopting a rigorous quantitative research approach to examine the practical implications of CMI in an environment characterized by resource constraints, rapid market dynamics, and diverse stakeholder expectations. The research places particular emphasis on Thai SMEs, serving as a microcosm to investigate the unique challenges and opportunities associated with the adoption of CMI. Rooted in the distinctive blend of traditional values and global economic integration that characterizes the Thai business landscape, this study employs surveys, interviews, and performance metrics to gain a nuanced understanding of the socio-cultural awareness within the region and its implications for organizational behavior. Acknowledging that the implementation of CMI in Thai SMEs presents distinct challenges, including the impact of traditional hierarchical structures on the dissemination of ethical values across organizational levels, this research recognizes the interconnectedness between these challenges and the broader economic context in Thailand. The quantitative research approach entails the distribution of structured surveys to a representative sample of SMEs across diverse sectors in Thailand. This instrument assesses the degree of CMI within organizations, the integration of ethical considerations into HR practices, and the perceived impact on organizational agility, taking into account the nuances of the Thai economic landscape. Rigorous statistical analyses, including correlation and regression, ensure a comprehensive examination of potential relationships between CMI, SHRD, and OA. The use of established scales for measuring ethical climate, human resource development practices, and organizational agility enhances the reliability and validity of the research findings. The implications of this research extend to both the academic and practitioner communities. For practitioners, especially SME leaders, this study offers practical insights into the tangible benefits and challenges associated with adopting CMI, enabling informed decision-making and the cultivation of sustainable business practices within the dynamic Thai business environment. Subsequent chapters of this dissertation will delve into the research design, data collection methods, and analysis procedures, providing a comprehensive and nuanced exploration of CMI within the ever-evolving landscape of Thai SMEs, with due consideration to the broader economic and organizational context.